Lenalidomide in patients with POEMS syndrome: a systematic review and pooled analysis. Issue 9 (September 2014) - Zagouri, Flora; Kastritis, Efstathios; Gavriatopoulou, Maria; Sergentanis, Theodoros N.; Psaltopoulou, Theodora; Terpos, Evangelos; Dimopoulos, Meletios-Athanasios
Abstract The purpose of this pooled analysis was to synthesize all available data so as to evaluate the efficacy and safety of lenalidomide in patients with POEMS syndrome. Eligible articles were identified by a search in MEDLINE and ClinicalTrials.gov databases using a predefined combination. Eligible cases of patients treated in our department were additionally included. Overall, 51 patients were included. The median age of patients was 54.5 years (range: 32–79 years). Lenalidomide was given as first- or second-line treatment in 28.6% and 47.6% of patients, respectively. Hematological responses included complete response in 18.6%, very good partial response in 39.5% and partial response in 37.2% of cases. Vascular endothelial growth factor (VEGF) reduction was reported in all cases. Neuropathy improved in 92.0% of cases and stabilized in 8%. The progression-free survival (PFS) estimate at 12 months was 93.9%. Lenalidomide can represent a safe and effective option for the treatment of patients with POEMS.